Safety and Effectiveness of Short-Course AmBisome in the Treatment of Post–Kala-Azar Dermal Leishmaniasis: A Prospective Cohort Study in Bangladesh. (15th March 2018) - den Boer, Margriet; Das, Asish Kumar; Akhter, Fatima; Burza, Sakib; Ramesh, V; Ahmed, Be-Nazir; Zijlstra, Eduard E; Ritmeijer, Koert
Abstract: Background: A safe and effective short-course treatment regimen for post–kala-azar dermal leishmaniasis (PKDL) is considered essential for achieving and sustaining elimination of visceral leishmaniasis (VL) in the Indian subcontinent [1, 2 ]. Here, single-dose liposomal amphotericin B (AmBisome) has been adopted as a first-line regimen for VL; however the effectiveness and safety of AmBisome for PKDL has not been formally evaluated. Methods: The safety and effectiveness of AmBisome 15 mg/kg, given over 15 days in 5 biweekly infusions of 3 mg/kg on an outpatient basis, was evaluated between April and November 2014 in patients with clinically diagnosed PKDL, aged ≥12 years and residing in a highly VL-endemic area in Bangladesh. This was a prospective cohort observational study, with the objective to assess final cure 12 months after treatment. Clinical response was monitored at 1, 3, 6, and 12 months, and safety during treatment and up to 1 month after treatment. Results: Of the 280 patients meeting the inclusion criteria, 273 were assessed at 12 months. A complete or major improvement of lesions was seen in 245 patients (89.7%); 213 (78.0%) were considered completely cured. Lesions did not improve in 28 (10.3%) and new lesions appeared in 13 (4.8%). All patients completed treatment without severe or serious adverse events. Conclusions: A short-course 15-mg/kg AmBisome regimen proved safe and effective in the treatment of clinically diagnosed PKDL in Bangladesh, and should be considered a treatment option for routine programmatic use in the VL elimination effort in the Indian subcontinent. Abstract : A short-course treatment regimen of AmBisome, 15 mg/kg in 5 doses, was found effective and safe in patients with post–kala-azar dermal leishmaniasis in Bangladesh in a prospective cohort observational study, with final cure assessed 12 months after treatment.